Research on dynamical properties of a three-wheeled electric vehicle from the point of view of driving safety - Blatnický Miroslav; Dižo Ján; Suchánek Andrej; Šťastniak Pavol (Open Engineering, 2023)
Many vehicles in urban and suburban environment are occupied just by one passenger, i.e. by a driver. Therefore, it is worth to think about vehicles, which would be smaller and lighter and which would include environmental-friendly power source. One such vehicle is the presented three-wheeled electric vehicle. This vehicle is designed for one passenger and it is powered by an ecologic electric powertrain. Therefore, it is necessary to research its driving properties. There are two types of vehicle designs, an original design and a modified design with a reworked body. Both are characterised by the symmetrical distribution of the mass to the longitudinal axis. In terms of driving properties of the vehicle, overturning stability during cornering and vertical dynamics in terms of safety are assessed for both original and modified designs. The article presents the main description of the original and modified designs of the three-wheeled vehicle and results from simulation computations focused on analysis of the over-turning stability. It has been revealed that the original vehicle, which is lighter, has better dynamical properties in curves with regards to driving and the higher total weight of the modified vehicle is safer in terms of vertical dynamics.